Application of Early Childhood Learning Model with Gender Justice - Adriany, Vina; Widaningsih, Lilis; Yulindrasari, Hani; Aryanti, Tutin; Shantini, Yanti (Universitas Pendidikan Indonesia (UPI), 2023)
This community service program is a follow-up to the programs and activities carried out in Batu Karut Hamlet, Cibeureum Wetan Village, Cimalaka District, Sumedang Regency. This program was created to maintain the sustainability of community empowerment activities through activities to strengthen the competence of ECCE practitioners as an effort to optimize the delivery of community education services, especially early childhood education. The target in this service is to increase the competence of ECCE practitioners in Cibeureum Wetan Village, especially the professional competence of ECCE practitioners related to the realization of gender-equitable ECCE education. The method used in community service for this Assisted Village is the Participatory Rural Appraisal (PRA) method based on local partnerships and potential. This method has an emphasis on community involvement in the overall activity. This model is carried out by identifying community problems and needs, planning activities with the community through FGD (Focus Group Discussion), preparing training activities, carrying out training activities for ECCE practitioners, implementing gender-sensitive ECCE learning models carried out by ECCE practitioners who have received training, evaluation and monitoring carried out by the service team by listening to the reflections of ECCE practitioners related to implementation The learning model in question.